New Approach to Structure–Property Correlations of Different Films of Sorbitan Esters and Their Self‐Assembly into Viscoelastic Monolayers. Issue 3 (1st February 2019) - Demand, Sarah; Egger, Simon; Degen, Patrick; Salmen, Paul; Paulus, Michael; Tolan, Metin; Rehage, Heinz
Abstract: This publication is focused on the structural origin of viscoelasticity in Langmuir monolayers. To improve the understanding of the structural origin of viscoelasticity of surfactant films, we systematically studied interfacial films of different sorbitan esters with saturated (Span 60 and 65) and unsaturated (Span 80 and 85) paraffin chains by means of surface rheology, Langmuir isotherms, X‐ray reflectometry (XRR), and Brewster angle microscopy (BAM). The results of two‐dimensional shear rheological measurements revealed the existence of temporarily cross‐linked networks. In dynamic BAM experiments, we observed a swinging motion of the monolayers as a result of a sudden externally initiated mechanical perturbation. The viscoelastic film response, which relaxed with time as the external force vanished, could be traced back to the presence of foam‐like supramolecular structures that interlinked solid‐condensed domains. The temperature dependence of the elastic response implied that the solid domains decomposed at temperatures close to the bulk melting point of Span 60 and Span 65. We concluded that insoluble surfactants formed solid domains at the interface, which were linked with each other by nonsolid areas, giving viscoelastic films. These newly discovered insights into coherent film formations could provide new opportunities for designing mechanically stable surfactant interfaces. Abstract :